Analisis Nyanyian Pujian Daud Dan Relevansinya Bagi Pemuda Masa Kini ( 1 Tawarikh 29:10-19) - Lela Siska Inriani Samosir; Susilawati Panjaitan; Herdiana Br Hombing (Jurnal Magistra, 2023)
"The song of praise holds high religious value, as earnest singing is considered equivalent to praying twice. A song of praise holds its own significance within the order of Christian worship, even within the liturgy of Christian services. The literary detective method used by the author aims to review theological studies on the analysis of David's song of praise and its relevance to the youth of today (1 Chronicles 29:10-19). This research yields the attitude that a Christian youth should possess in viewing songs of praise, and how the creed of Christian youth influences the praising and worshiping of the name of the Lord."